2018
DOI: 10.1111/cga.12320
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a thoracolumbar supernumerary rib in rat developmental toxicity studies: A short discussion on the critical window

Abstract: Thoracolumbar supernumerary ribs (TSRs) are classified as less severe skeletal anomalies in rat developmental toxicity studies, although their incidence is relatively high in rodent studies. To investigate the characteristics of the critical window for chemically-induced TSR, in this study, rats were administered 5-fluorocytocine (5-FC) or sodium salicylate (SAL) at one of three time periods on gestational day (GD) 9, early morning (7:00 AM), midday (12:00 PM to 1:00 PM), or late afternoon (4:00 PM or 7:00 PM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We have reported that TSR (both short and full length) was induced in rat fetuses by single oral administration of 75 mg/kg 5-FC on GD9, without affecting maternal clinical signs, reproductive performance such as the number of implants, or fetal development (Kuwagata et al, 2018a).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have reported that TSR (both short and full length) was induced in rat fetuses by single oral administration of 75 mg/kg 5-FC on GD9, without affecting maternal clinical signs, reproductive performance such as the number of implants, or fetal development (Kuwagata et al, 2018a).…”
Section: Discussionmentioning
confidence: 97%
“…A previous study investigating the origin of thoracolumbar supernumerary ribs (TSR, 14th rib) in rats showed that oral administration of 75 mg/kg 5-FC to pregnant rats on gestation day (GD) 9 induced TSR (Kuwagata et al, 2018a). Furthermore, oral administration of 5-FC to pregnant rats on GD13 induced the formation of abnormal digits.…”
Section: Introductionmentioning
confidence: 99%